2020
DOI: 10.1016/j.jhydrol.2020.125369
|View full text |Cite
|
Sign up to set email alerts
|

Induced polarization as a tool to characterize shallow landslides

Abstract: The development of shallow landslides is strongly connected to the changes in the water content of soils on hillslopes, their clay content and permeability distribution, which, in turn, are playing an important role regarding their hydro-mechanical properties. A non-intrusive geophysical method able to map these properties would be very helpful. The most common geoelectrical method, DC (Direct Current) resistivity, cannot be used as a stand-alone technique for this purpose since it depends on two contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…With the exception of certain models in the ERI series, which are associated with poor raw data quality (particularly in 2018 when the number of TR measurements drops off significantly), the time-series analysis could be taken further with petrophysical relationships between resistivity, moisture content (Uhlemann et al 2017) and other critical parameters for assessing slope stability such as soil suction (Crawford and Bryson 2018). Alternatively, more involved workflows could conceivably couple hydrological and geoelectrical modelling through petrophysical relationships (Johnson et al 2017;Revil et al 2020), allowing for robust assessments on the slope hydrogeology through time.…”
Section: Workflowmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of certain models in the ERI series, which are associated with poor raw data quality (particularly in 2018 when the number of TR measurements drops off significantly), the time-series analysis could be taken further with petrophysical relationships between resistivity, moisture content (Uhlemann et al 2017) and other critical parameters for assessing slope stability such as soil suction (Crawford and Bryson 2018). Alternatively, more involved workflows could conceivably couple hydrological and geoelectrical modelling through petrophysical relationships (Johnson et al 2017;Revil et al 2020), allowing for robust assessments on the slope hydrogeology through time.…”
Section: Workflowmentioning
confidence: 99%
“…Numerous studies have shown that electrical resistivity imaging (ERI), also known as electrical resistivity tomography (ERT), can be an invaluable aid in interpreting changes in near surface hydrologic conditions (Binley et al 2015;Brunet et al 2010;Chambers et al 2014;Johnson et al 2017;McLachlan et al 2020;Perrone et al 2014;Revil et al 2020;Uhlemann et al 2017;Uhlemann et al 2016b). In the absence of any changes to geological structure, changes in electrical resistivity should be due to changes in temperature and the pore fluid (saturation/salinity) in the subsurface (Waxman and Smits 1968).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IP measures the degree to which the subsurface is polarized (somewhat like a capacitor) on application of an electric field; this polarization foremost exists due to the restricted movement of ionic charges in the EDL lining pore throats (or surrounding mineral grains). In soils/rocks devoid of electronically conducting minerals, IP measurements are directly proportional to the surface conductivity term (Equation (4)), meaning that IP measurements can reduce the inherent ambiguity of resistivity interpretation (Revil et al, 2020; Slater & Lesmes, 2002; Zarif, Kessouri, & Slater, 2017). The presence of electronically conducting (or semiconducting) minerals results in a much stronger polarization signal due to larger restricted movement of ionic charges surrounding the mineral in response to the polarization of charges inside the electron conductor.…”
Section: Future Prospects and Challengesmentioning
confidence: 99%
“…a mechanistally based and testable model to understand induced polarization (Revil et al, 2017a), which is simple enough to be applicable in field conditions (Revil et al, 2020).…”
Section: Petrophysicsmentioning
confidence: 99%